Post-stem cell transplant maintenance for pediatric acute leukemias: insights from a Brazilian institution with a Latin American perspective - Breviglieri, Carla Nolasco Monteiro; Gouveia, Roseane Vasconcelos; Ginani, Valéria Cortez; Santos, Camila Noronha; de Oliveira, Milena Reis Santos; Batalha, Anna Beatriz Willemes; de Alencar, Gabriella Sayuri; Goto, Edna Harumi; Marques, Juliana Francielle; Pupim, Marcia Puato Vieira; Seber, Adriana (Frontiers in Oncology, 2025)
IntroductionIn resource-limited countries, access to advanced therapies like CAR T-cell therapy is often unattainable. Clinical trials face challenges, with pediatric populations frequently excluded or experiencing significant delays. This highlights the need for alternative strategies to address high relapse risks in pediatric acute leukemia post-stem cell transplant.MethodsThis retrospective study included pediatric acute leukemia patients who underwent HSCT between 2014 and 2024. Post-HSCT maintenance therapy became standard practice in 2021, utilizing agents like venetoclax, decitabine, azacitidine, blinatumomab, DLI, and targeted therapies. Primary outcomes were overall survival (OS) and disease-free survival (DFS); secondary outcomes included relapse rate and treatment-related toxicities.ResultsAmong 94 patients (64 with ALL, 30 with AML), ALL patients receiving maintenance therapy had an OS of 78% versus 47% without maintenance (p=0.02); DFS was 64% with maintenance and 45% without (p=0.12). In AML patients, maintenance was associated with an OS of 88% compared to 27% without. Relapse rates decreased in maintenance-treated patients, especially among AML patients with pre-transplant MRD positivity. Treatments were generally well-tolerated, with manageable toxicities.DiscussionPost-HSCT maintenance therapy is feasible in resource-limited settings and may improve survival outcomes. Strategies like hypomethylating agents with venetoclax in T-ALL and post-HSCT blinatumomab in B-ALL show potential benefits. Challenges include drug access and standardizing protocols. Further trials are needed to validate these findings in low- and middle-income countries.